Reimagining Islamic Philanthropy in the Digital Economy: A Comparative Analysis of Branding as Ethical Capital in Private and State-Owned Institutions - Muhammad Deni Putra; Aziz Muslim; Mukhamad Yazid Afandi; Abdullah Sahroni; Muhammad Kamil Husain; Sari Utami (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
This qualitative library research examines the contrast in social media branding effectiveness between private and state-owned Islamic philanthropic institutions, an important issue in the digital era where public trust and engagement are essential. Using a systematic thematic analysis of scholarly literature published between 2014 and 2024, the study finds that private institutions consistently outperform their state-owned counterparts by leveraging organizational agility, innovative storytelling, and transparent communication. These practices are further interpreted as contemporary manifestations of core Islamic values, namely amanah (trust) and ihsan (excellence). The primary objective of this study is to identify the underlying factors contributing to this disparity and to generate actionable insights for optimizing digital outreach in Islamic philanthropy. The findings suggest that effective branding is not merely a technical advantage but also reflects a deeper institutional alignment with ethical principles, enabling private institutions to build stronger community engagement and donor loyalty. Accordingly, this study offers important implications by proposing a transformative approach through which state-owned institutions can adopt value-based digital strategies to enhance transparency, public appeal, and overall social impact, thereby strengthening the Islamic economic ecosystem in the twenty-first century.